The Issue of International Legal Regulation of the Exploiting Natural Resources in Outer Spaceon the Basis of International Law - R. Sh. Radzhabova (Теоретическая и прикладная юриспруденция)
The article analyzes the problem of international legal regulation of the exploiting natural resources in outer space. Special attention is paid to innovative proposals to amend current legislation offered by ague Space Resources Governance Working Group and Space Generation Advisory Council. The need to establish a distinction between the legal regimes of celestial bodies and resources of outer space is emphasized. Arising from the research, a conclusion about the need to update the existing rules of international space law and concretize the concepts such as celestial bodies, space resources, common heritage of mankind and use of outer space is formulated.